Association of Prestroke Glycemic Control With Vascular Events During 1-Year Follow-up. (26th October 2021) - Chang, Jun Young; Kim, Wook-Joo; Kwon, Jee Hyun; Lee, Ji Sung; Kim, Beom Joon; Kim, Joon-Tae; Lee, Jun; Cha, Jae Kwan; Kim, Dae-Hyun; Cho, Yong-Jin; Hong, Keun-Sik; Lee, Soo Joo; et al.
Abstract : Background and Objectives: We evaluated the association between admission glycated hemoglobin (HbA1c) and subsequent risk of composite vascular events, including stroke, myocardial infarction (MI), and vascular death, in patients with acute ischemic stroke and diabetes. Methods: Patients who had a TIA or an acute ischemic stroke within 7 days of symptom onset and diabetes were included in a retrospective cohort design using the stroke registry of the Clinical Research Center for Stroke in Korea. The association between admission HbA1c and composite vascular events, including stroke, MI, and vascular death, during 1-year follow-up was estimated using the Fine-Gray model. The risk of composite vascular events according to the ischemic stroke subtype was explored using fractional polynomial and linear-quadratic models. Results: Of the 18, 567 patients, 1, 437 developed composite vascular events during follow-up. In multivariable analysis using HbA1c as a categorical variable, the risk significantly increased at a threshold of 6.8%–7.0%. The influence of admission HbA1c level on the risk of composite vascular events was pronounced particularly among those in whom fasting glucose at admission was ⩽130 mg/dL. The optimal ranges of HbA1c associated with minimal risks for composite vascular events were lowest for the small vessel occlusion subtype (6.6 [95% confidence internal [CI], 6.3–6.9]) compared to the large artery atherosclerosis (7.3 [95% CI, 6.8–7.9]) or the cardioembolic subtype (7.4 [95% CI, 6.3–8.5]). Dicussion: In patients with ischemic stroke and diabetes, the risks of composite vascular events were significantly associated with admission HbA1c. The optimal range of admission HbA1c was below 6.8%–7.0% and differed according to the ischemic stroke subtype.